The internationalization of the curriculum: The perspective of professors at the University of Guadalajara - Nigra, Sabrina (2024)
A study on teaching competencies and curriculum internationalization in a Mexican university is presented. To achieve this, a review of the literature on internationalization of higher education, teaching competencies and internationalization of the curriculum was carried out. The methodological design used was qualitative. First, a content analysis of reports and documents was carried out; subsequently, a survey was applied to the teachers of the University Center of Economic and Administrative Sciences of the University of Guadalajara to learn about their perceptions regarding the internationalization of the university and teaching. It was concluded that in the aforementioned institution, the internationalization of the curriculum is still at an initial stage and it is necessary to promote measures aimed at the institutional internationalization of teaching so that there is an impact on the curricula of the subjects that include interdisciplinarity and multiculturalism as needed in today's education, which demands teachers with an international profile.